FUNGSI GEREJA BATAK KARO PROTESTAN (GBKP) DALAM MELESTARIKAN BUDAYA BATAK KARO DI KOTA DENPASAR - Putra Ketaren, Firmansyah (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Bali is an island which the majority of its people embrace Hindu religion. However, in Bali also there are people who embrace other religions such as Islam, Catholic and Christian Protestant. In Denpasar there is Batak Karo Christian congregation who do not want to live side by side with the others. They even seem to self exclusive. The church is called the Church of Batak Karo Protestant runggun Denpasar. From the elaboration above, in this research the issues which will be examined defined as follows : what is the function of the Church of Batak Karo Protestant for the congregation. The research is conducted with the purposes of to find out the fuction of the Church of Batak Karo Protestant for its congregation. The research is conducted by using qualitative method, which being analyzed with functional theory of Malinowski. The result of research shows that the congregation of Batak Karo church built their own church and lived exclusively in worshipping because they do not want to feel strange in other people’s region. The function of establishing GBKP for Batak Karo congregation shows that with the existence of the church the social ties, solidarity, identity and a sense of togetherness for fellow Batak Karo congregation can always be maintained sustainably to date. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: function, Church, Batak Karo.